The influence of cultural belonging on social distances in native and international students from the Republic of Moldova / Influența apartenenței culturale asupra distanțelor sociale la studenții autohtoni și internaționali din Republica Moldova - RUSNAC Svetlana; KHORY Johnny (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The research presented in this article was carried out in order to identify the influence of cultural belonging on the social distances between host country and international students from the Republic of Moldova. The data were collected by applying the Social Distance Scale developed by Emory S. Bogardus. The sample consisted of 319 subjects, of which 159 (49.8%) are international students, 160 (50.2%) - natives, aged between 18 and 35, representing various countries, some of them with quite a different culture from that of the host country: People's Republic of China, Democratic Republic of Congo, South Korea, Israel, Romania, Republic of Turkey, Ukraine. The use of the Bogardus scale indicated different social distances for domestic and international students. Students from the host country (2.7), followed by those from Romania (3.3), Ukraine (3.3), adopt the smallest distances of social contact with exponents of the other 7 countries. Average social distances adopt students from Israel (3.6), Republic of Turkey (3.5), Democratic Republic of Congo (3.8), South Korea (3.6), People's Republic of China (3.5). We note that there are differences in culture, denomination, but also in knowledge and experiences of communication with the representatives of other countries. The variable "year of study" has an important role in establishing social distances. With communication and getting to know another, social distances become smaller. The social distances between international students and the local population are within the average range, which means that they did not experience serious relationship problems. Secondly, even if cultural differences influence social distances, some of the international students, coming from countries with different cultural and confessional characteristics from that of the Republic of Moldova, do not radically distance themselves from the local population, they are open to communication and relationships with students from countries with a culture similar to that of the host country - Romania and Ukraine. It seems that the most important factor in maintaining social distances is communication differences. Engaging both native and international students in curricular and extracurricular activities can determine them to enjoy mutually beneficial experiences. Furthermore, universities should not only develop superficial internationalization policies, but ensure that all students are involved so that they can contribute to them.